Design and development of a high efficiency tank for crude oil dehydration (I) - Forero, Jorge Enrique; Ortíz, Olga Patricia; Nariño, Fredy Abelardo; Díaz, Javier; Peña, Hermes (CT&F - Ciencia, Tecnología y Futuro, 2008)
This paper introduces a new tank design for dehydrating and desalting large volumes of crude oils previously degasified, crude oil dehydration efficiency is reduced by gas presence in the emulsion interphase. The design presented in this paper is versatile (it is adaptable to any classical dehydration process), highly efficient in terms of separation (values usually greater than 90% and/or treated crude oil BSW less than 0,5% are ensured), low installation and operation costs, less consumption of additives. These are some of the advantages found in pilot tests plants and proven in industrial systems at the Ecopetrol S.A. production fields with treatment capacities from 14 to 50 KBD. Although this process also can be applied to other ranks of flow, maintaining the design critical conditions of each case in particular. This system does not exhibit the typical limitations shown by treatment tradicional systems (FWKO, Gun Barrel, thermal and electrostatic separators, etc.) (Al-Ghamdi, 2007) since it can be easily adapted to system treatments for light, intermediate, and heavy crude oils and to treatments with BSW content ranging from a very low levels of < 1% to very high levels > 95%, values that are not unusual in production fields nowadays, especially where accelerated production methods are used.